Does export product quality and renewable energy induce carbon dioxide emissions: evidence from leading complex and renewable energy economies - Wang, Zhijian (2021)
This study investigates the dynamic interdependence between CO2 emissions, real gross domestic product (GDP), renewable and non-renewable energy generation, urbanization, and export quality for both the top ten renewable energy and top ten economic complexity index (ECI) countries. The techniques of panel cointegration, long-run FMOLS, DOLS, and Granger causality are used spanning the period 1980–2014. Long-run estimates suggest that, for the top ten renewable energy countries, only renewable energy generation contributes to mitigating CO2 emissions, while the other variables lead to increase emissions levels in the long-run. However, for the case of leading complex economies, the empirics highlighted the significant role of renewable energy in carbon mitigation. Exports quality leads to decrease emissions level and real GDP, non-renewable energy and urbanization contribute to the rise in emissions. Interestingly, for the top ten renewable energy countries, Granger causality analysis mentioned a two-ways short-run relationship between renewable energy generation and export quality and one-way causality from export quality to CO2 emissions. The findings mention that adopting clean technologies using renewable energy might act as a key tool for export quality improvement and mitigation of CO2 emissions. Results are related to Sustainable Development Goals (SDG-7: using more renewable, affordable energy; SDG-8: sustainable economic growth and decent employment for all, SDG-13: regulating emissions and promoting renewable energy) and discussed in this sense.